Alfalfa haylage for sows during gestation - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1981)
Digestion and nitrogen retention studies suggest that three pounds of good quality alfalfa haylage dry matter and two pounds of a grain, mineral, and vitamin premix will meet the nutritional requirements of sows during gestation. Quality of the haylage is extremely important for sows. Third-cutting alfalfa had a higher digestible energy and digestible protein than did the more mature first-cutting haylage. The digestible energy of alfalfa haylage for sows was 954 to 1,096 Kcal/pound. Sows fed alfalfa haylage and ONLY ONE pound of a grain vitamin and mineral premix farrowed pigs that were lighter at birth than pigs farrowed from sows fed 4Â½ pounds of a corn-soy diet during gestation.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Alfalfa; Gestation